Performance Analysis Of Islamic Religious Education Teachers In School Learning - Subakri Subakri (Fenomena, 2023)
The existence of Islamic Religious Education (PAI) teachers is expected to help form students who have high competitiveness while still practicing Islamic teachings. However, the irony is that the time allocation for Islamic religious education subjects in public schools is minimal, especially in Vocational High Schools (SMK), which incidentally focuses more on each vocational field and is supplemented by the Field Work Practice (PKL) program with a lot of time. That consciously requires Islamic religious education teachers to have effective and efficient classroom learning strategies, including organizing and managing so that the material being taught is conveyed correctly and optimally. This study aims to determine PAI teachers' effectiveness in planning, implementing, and evaluating them in class. This study used a qualitative method with a type of field research and used descriptive data analysis to validate the data using source and technique triangulation. This study's results indicate that the effectiveness of teacher performance in planning, implementing, and evaluating is the same as in general. After conducting the Teacher Performance Assessment, it turns out that in class implementation, several teacher competencies need to be improved, such as mastering material, structure, and concepts in class. So, the institution provides facilities to teachers to enhance their teaching performance further with the In-house Training (IHT) program.